EFEKTIVITAS APLIKASI PENDAFTARAN ANTRIAN PASPOR ONLINE DI KANTOR IMIGRASI KELAS 1 TPI (TEMPAT PEMERIKSAAN IMIGRASI) KOTA SAMARINDA PROVINSI KALIMANTAN TIMUR - Harmitalia, Mita; Irawan, Bambang; Khaerani, Thalita Rifda (Jurnal Ilmu Administrasi Negara (JUAN), 2022)
Currently, the world is experiencing an era of disruption. This encourages changes in public sector business processes that impact old business models that must be adapted to the times, so service ideology must also follow the technological era. This study aimed to analyze the effectiveness of using an online registration application at the Kantor Imigrasi Kelas I TPI Samarinda. The method used in this study uses a qualitative descriptive approach with observation, interviews, and documents techniques. It uses the Mary de Chesnay Qualitative Data analysis model with the stages of data collection, raw data description, data reduction, data categorization, and constructing categorical relationships. The results showed that the implementation of APAPO at the Kantor Imigrasi Kelas 1 TPI Samarinda has been running effectively. This is illustrated by the absence of queues, the quota of passport applicants at APAPO provided is always available, and there is no brokering practice. APAPO outreach has been held through social media such as Instagram, Facebook, Twitter, and on print media in the form of newspapers, brochures, pamphlets, banners, and display screens. The existence of APAPO at the Kantor Imigrasi Kelas 1 TPI Samarinda really helps the community be more effective in making passports and becomes more efficient because it saves time and costs compared to before using the offline queue. Another finding that is no less important is that there are inhibiting factors in applying APAPO. At the same time, the obstacles are network quality constraints, applications that sometimes error, websites that cannot be reached to register online, and APAPO, which can only be uploaded via mobile phones with the Android system and literacy. Digital society is still low.